Transparansi Digital dalam Pembulatan Harga di Market Place Shopee: Standarisasi Praktik Pembulatan Berbasis Syariah - Shofa Robbani; Ana Mar'atus Safitri; Silvina, Anida Ulya; Sholikhah, Ria Ardaniatus; Putra, Sendy Nova Airlangga (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
This study examines the practice of price rounding in the Cash On Delivery (COD) payment system on the e-commerce platform Shopee, highlighting issues of information transparency and its compliance with the principles of Islamic economic law. The main issue raised is the lack of notification to consumers regarding price rounding by couriers, which can lead to injustice and financial losses. This research aims to determine the compatibility of such practices with the principles of fairness, transparency, and mutual consent as outlined in applicable Islamic law. This study employs a normative-empirical legal method with a qualitative approach, combining a literature review of Sharia principles with empirical data from observations and interviews in the Sumberrejo area, Bojonegoro. The research findings indicate that the practice of rounding prices without consent or notification to consumers violates the principles of transparency, fairness, and willingness (an-taraḍin) in Islamic law. However, if the rounding is done openly and with the consent of the consumers, it may still be acceptable under the principles of Islamic economic law. This research recommends the importance of developing Sharia-based ethical standards in e-commerce transactions that ensure transparency of information and fairness for all parties.